TAM’s Influence on Behavioral Intention to Use M-Din Mobile Banking Usage in West Java - Erick Ermawan; Ronny Samsul Bahri (PT. Banjarese Pacific Indonesia, 2025)
This study examines the influence of the Technology Acceptance Model (TAM), focusing on Perceived Ease of Use (PEOU) and Perceived Usefulness (PU), on users’ Behavioral Intention (BI) to adopt and continue using M-Din, a Sharia-based mobile banking application at Bank Muamalat in West Java. Employing a quantitative survey of 100 active M-Din users, data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that PEOU significantly affects PU, and both PEOU and PU significantly influence BI; additionally, PU partially mediates the effect of PEOU on BI. This research contributes to the digital banking literature by reaffirming TAM constructs within an Islamic finance context and offers practical recommendations for optimizing Sharia-compliant mobile banking strategies. Implications for enhancing user interface design and promoting key features to boost adoption are discussed.